Paradigma Peran Regulasi tentang Hak Asasi Manusia dalam Penanganan Tindakan Terorisme sebagai Ancaman Kedaulatan Negara - Haslindra, Dinda Nopriansary; Arisani, Muhammad Hakim; Zahra, Afifah; Tricahyani, Sofie Indah; Ilham, Muhammad; Ramadhansyah, Muhammad Rangga (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
When acts of terrorism emerge in a country, they certainly pose a great danger to the security and tranquility of the government and its citizens. Terrorist acts that tend to be inhumane are considered actions that are contrary to the 1945 Constitution of the Republic of Indonesia. However, on the other hand, terrorism itself is also considered as a human issue, so when they still hold the status of a suspect, they must also be protected by law and should not be subjected to discriminatory treatment by law enforcement officials handling them, in accordance with the 1945 Constitution, specifically Article 28D. Criminal law also requires the principle of equality before the law for anyone still in the status of a suspect as a guarantee of protection. All countries have limitations, and Indonesia itself prohibits illegal firearms. Terrorism itself is prohibited and carries the heaviest penalty, which is the death penalty, in accordance with Law Number 5 of 2018, which essentially restricts a person's right to live. Because the law states that humans must respect the rights of other humans. However, duty is above all else, so before citizens have the right to various freedoms, they must fulfill their duties according to the existing regulations. So, as a consequence of their actions that often contradict the obligations set by the law, the death penalty is the appropriate measure. Because Indonesia considers the theory of relativism as a limitation of rights, the death penalty should not be regarded as an evil thing.